Effect of Distribution Resources Planning (DRP) Method on Supply Chain Management (SCM) - Yuli Setiawannie; Nita Marikena (IJISTECH (International Journal of Information System and Technology), 2023)
PT. Growth Asia is an industrial company in the iron and steel foundry sector. It is well known for its export orientation as a supplier of wear-resistant parts to the international market, especially in gold and copper mining. This steel product will be used for planning distribution activities in mining, with the primary raw material, namely scrap (old iron or scrap iron) obtained from domestic suppliers, which is then processed into finished products, namely selections (mining tools), and distributed to the distribution center. namely Gorontalo, Maluku, Papua, and South Kalimantan. Fulfilling consumer demand for the product is not timely; this occurs due to problems in the distribution schedule at the distribution center to each city that is a consumer of PT. Growth Asia. Based on these problems, the purpose of this study is to determine the factors that cause non-smooth distribution, determine distribution scheduling planning using the Distribution Resources Planning (DRP) method and its effect on supply chain management method that can be proposed to deal with this problem is Distribution Resources Planning (DRP). With DRP, companies can initiate distribution scheduling more accurately and, at the same time, achieve production stability. The results of distribution planning and scheduling with the DRP method can reduce the total frequency of orders from 20 orders to 13 demands, and distribution costs have decreased by 13%, from IDR 39,610,000 to IDR 26,159,000.